2010
DOI: 10.2165/11311980-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between an Oxidative Stress Biomarker and Plasma Haemoglobin in Patients with Chronic Kidney Disease

Abstract: Introduction Evidence suggests that decreased haemoglobin plasma concentration may be a predictor of adverse cardiovascular events in patients with chronic kidney disease (CKD). We hypothesized that in CKD patients, oxidative stress could influence the development of cardiovascular damage via a relationship with haemoglobin levels.\ud \ud Methods We assayed plasma levels of the biomarker of oxidative stress 8-ISO-prostaglandin F2α (8-ISO-PGF2α) and of haemoglobin in 193 stage 2-5 CKD patients, investigating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Mattsson et al [6] observed elevated levels of F 2 -isoprostanes in the CSF of patients with multiple sclerosis. Using plasma F 2 -isoprostane levels as a metric, Riccobene et al [7] determined that patients with chronic kidney disease are more likely to endure atherosclerotic processes brought about by oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…Mattsson et al [6] observed elevated levels of F 2 -isoprostanes in the CSF of patients with multiple sclerosis. Using plasma F 2 -isoprostane levels as a metric, Riccobene et al [7] determined that patients with chronic kidney disease are more likely to endure atherosclerotic processes brought about by oxidative stress.…”
Section: Introductionmentioning
confidence: 99%